DAYA ANTI QUORUM SENSING EKSTRAK DAUN KAYU MANIS (Cinnamomun burmannii Ness. Ex Bl.) TERHADAP Pseudomonas aeruginosa - Fitri Apriliany; Hady Anshory; Triana Hertiani (Faculty of Pharmacy, Universitas Gadjah Mada, 2013)
Quorum sensing is a communication system among bacterial cells which correlates with biofilm formation. Biofilm can protect bacteria from environment including antibiotic of which can cause higher antibiotic concentration of 100 up to 1000 times. Inhibition of quorum sensing is expected to inhibit the biofilm formation. The cinnamon bark (Cinnamomum burmanii Ness. Ex Bl.) has been known to have antibacterial and antibiofilm activities. Leaves are available abundantly which urges a research to find out the activity as anti quorum sensing against Pseudomonas aeruginosa. The succesive maceration of dried pulverized leaves produced hexane, ethyl acetate, and methanol extracts. Antibacterial activity was observed by microdillution method with MTT assay. Afterwards, the active extract was examined for anti quorum sensing activity by diffusion method in cetrimide Agar. Quorum sensing activity was shown by dark zone (opaque) growth around sample application, observed under UV light of 366 nm. TLC bioautography method was done to observe the active spots by using silica gel F254 as the stationary phase, chloroform-methanol (6:1 v/v) as the mobile phase, loading sample used was 1.25 mg and 30 min of plate contact duration. The ethyl acetate extract inhibited growth of P. aeruginosa with shown by MIC at 8 µg/µL Quorum sensing as well as growth inhibition activities were observed at loading samples 12,5 and 25 mg/wells, while at 6,25 mg the extract only exhibited quorum sensing inhibition. Presences of substances having phenolic, flavonoid, alkaloid and aldehyde/keton as functional groups were detected by TLC method of the extract but no active spot identified on bioautography.